2017
DOI: 10.1097/md.0000000000006429
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of exhaled nitric oxide concentration in patients with obstructive sleep apnea

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 44 publications
2
16
0
1
Order By: Relevance
“…Previous studies have found increased airway inflammation and effects on airway remodelling among subjects with obstructive sleep apnoea, and treatment with positive airway pressure may diminish the airway inflammation. This makes it plausible that sleep disordered breathing may affect the lung function [6, 27]. Our study adds that even habitual snoring in the general population may have detrimental effects on lung function over time.…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies have found increased airway inflammation and effects on airway remodelling among subjects with obstructive sleep apnoea, and treatment with positive airway pressure may diminish the airway inflammation. This makes it plausible that sleep disordered breathing may affect the lung function [6, 27]. Our study adds that even habitual snoring in the general population may have detrimental effects on lung function over time.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, our study indicated that FeNO values were not significantly different in those patients with or without OSA. Studies investigating the effect of OSA on FeNO measurements are inconsistent and with conflicting results [10][11][12][13][14][15][16][17][18][19]23]. Similar to our findings, a study [19] with 129 consecutive patients, aged ≥ 16 years, showed no value in incorporating FeNO in the screening of OSA, considering that FeNO values were similar among individuals with or without SDB, and also whether SDB was defined by an AHI threshold of ≥ 5.0/h or ≥ 15.0/h.…”
Section: Discussionmentioning
confidence: 99%
“…Fractional exhaled nitric oxide (FeNO) can be easily, rapidly, and non-invasively measured for assessment of airway inflammation, and is extensively used in asthma to evaluate both severity and therapeutic responses [7][8][9]. However, FeNO levels in OSA patients remain somewhat unclear [10]: both elevated FeNO [11][12][13][14][15] and unaltered FeNO levels [16][17][18][19] have been reported when comparing OSA patients to controls. A recent meta-analysis [10] addressed FeNO levels in patients with OSA and concluded that there was a significant increase in FeNO levels in subjects diagnosed with OSA.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations